To find the inverse of a function Switch the x and y Solve for y
Example 1 Means the inverse of g(x)
Example 2 Means the inverse of g(x)
Example 2 Continued Step 1 Find the inverse. Rewrite the function using y instead of f(x). Switch x and y in the equation. Cube both sides. Simplify. Isolate y.
Check It Out! Example 2 Continued Step 1 Find the inverse. y = x3 – 2 Rewrite the function using y instead of f(x). x = y3 – 2 Switch x and y in the equation. x + 2 = y3 Add 2 to both sides of the equation. Take the cube root of both sides. 3 x + 2 = y 3 x + 2 = y Simplify.